The dual effect of endoplasmic reticulum stress in digestive system tumors and intervention of Chinese botanical drug extracts: a review - Zhang, Jinlong; Chen, Yanyu; Chen, Bo; Sun, Dajuan; Sun, Zhen; Liang, Junwei; Liang, Jing; Xiong, Xin; Yan, Hua (Frontiers in Pharmacology, 2024)
Endoplasmic reticulum (ER) homeostasis is essential for maintaining human health, and once imbalanced, it will trigger endoplasmic reticulum stress (ERS), which participates in the development of digestive system tumors and other diseases. ERS has dual effect on tumor cells, activating adaptive responses to promote survival or inducing apoptotic pathways to accelerate cell death of the tumor. Recent studies have demonstrated that Chinese botanical drug extracts can affect the tumor process of the digestive system by regulating ERS and exert anticancer effects. This article summarizes the dual effect of ERS in the process of digestive system tumors and the intervention of Chinese botanical drug extracts in recent years, as reference for the combined treatment of digestive system tumors with Chinese and modern medicine.